Development of Alternative Foods using Local Ingredients as a Leading Culinary Tourism Product: A Taste Study of Swiss Roll Jackfruit Seeds and Dragon Fruit Skin - Rahayu, Enita (Media Wisata, 2025)
This study aims to develop Swiss roll by utilizing jackfruit seeds and dragon fruit skin as an alternative local food that is highly nutritious and becomes one of Indonesia's typical foods with local food ingredients that can be an attraction for tourists to taste the typical food. The research used is quantitative research with a hedonic panelist test. The time and place of the preliminary research and further research were carried out from January to March 2025 at the Tourism Department, Balikpapan State Polytechnic. The results of the average value of the taste of Swiss roll products with the use of jackfruit seed powder in the Swiss roll dough with dragon fruit skin as a filling. The results showed that the taste in F1 had an average value of 4.00, in F2 the average value was 3.90 and in F3 the average value was 3.27. It can be concluded that the most preferred by panelists was the F1 taste with an average value of 4.00. This product has proven to be acceptable to panelists and provides a highly nutritious food alternative based on local ingredients and can increase the appeal of tourists in the culinary field.